Knowledge, practices and regulatory challenges associated with portable handheld dental x-ray devices utilization among Indonesian dentists: a cross-sectional study - Nurrachman, Aga Satria; Ramadhani, Nastiti Faradilla; Wilujeng, Septia A.; Mazlan, Lailatul H.; Saputra, Deny; Ghazali, Ahmad Badruddin (Faculty of Dentistry, Hasanuddin University, Indonesia, 2025)
Objective: This study aimed to assess the knowledge of Indonesian dentists regarding the usage, safety practices, and regulatory frameworks for portable handheld dental X-ray devices. Material and Methods: A descriptive, cross-sectional study was conducted among dentists in Surabaya, Indonesia, between June and October 2024. A total of 1,770 dentists were invited to participate via an online questionnaire, with 184 completing the survey (10.4% response rate). The validated questionnaire assessed knowledge across 12 fields, each with subpoints. A Likert index percentage formula was used to quantify knowledge, and logistic regression analysis explored correlations between knowledge levels and professional characteristics. Results: Dentists’ overall knowledge was moderately low (44.9%). Ownership of handheld devices was associated with lower knowledge of licensing requirements (OR=0.089, p=0.002), radiation protective equipment (OR=0.122, p=0.016), and acrylic shielding plates (OR=0.214, p=0.041). Years of practice positively correlated with interest in purchasing devices (OR=2.230, p=0.020). Conclusion: Despite their benefits, portable handheld dental X-ray devices pose risks without proper training and adherence to regulations. Targeted education, standardized training, and regulatory clarity are essential to ensure safe and compliant use in clinical practice